Geology in primary education; Potential and perspectives - ΡΟΚΚΑ, Α. XP. (Bulletin of the Geological Society of Greece, 2018)
The factors which defined what Geological elements and how are being taught in Greek Elementary Schools are not only included in the National Curriculum Programs and in the Textbooks. The very few teaching hours of the subjects in which are included, the poor school-libraries and the absence of specialized training of the Primary schools teaching staff have an important role also. An additional role has the absence of modern thought for the specific problems of the Geological subject matter and the needs of educational process. This study deals with the evaluation and presentation of the Geological subject matter of the textbooks in Primary Education, as it is referred in Geography of the last two years in school. Also, the potentials and perspectives of enriching the Geological matter through the Textbooks "Study of the Environment", which are taught during the first four years of Primary schools are presented. Indicative examples on development and implementation of geological knowledge in practice are suggested, according the principles of Environmental Education, splendidly covering as well, the teaching and learning targets of this subject.